Safety evaluation of recombinant Newcastle disease virus expressing IBV multi-epitope chimeric live vaccine - Tan, Lei; Qiu, Xusheng; Liang, Lujing; Liao, Xin; Wang, Fei; Sun, Yingjie; Song, Cuiping; Liao, Ying; Ding, Chan (Frontiers in Microbiology, 2024)
Newcastle Disease (ND) and Infectious Bronchitis (IB) are two significant diseases that pose threats to the poultry industry, caused by Newcastle disease virus (NDV) and Infectious bronchitis virus (IBV), respectively. Currently, the control and prevention of these diseases primarily rely on vaccination. However, commercial ND and IB vaccines face challenges such as poor cross-protection of inactivated IBV strains and interference from live vaccines when used together, leading to immunization failures. Previously, we reported the successful rescue of a recombinant NDV expressing multiple epitopes of IBV, named rNDV-IBV-T/B, which showed promising immunoprotective efficacy against both NDV and IBV. This study focuses on the biosafety of the genetically modified recombinant vaccine candidate rNDV-IBV-T/B. Immunization was performed on day-old chicks, ducklings, goslings, and ICR mice. Observations were recorded on clinical symptoms, body weight changes, and post-mortem examination of organs, as well as histopathological preparations of tissue samples. The results indicated that the rNDV-IBV-T/B vaccine candidate had no adverse effects on the growth of targeted animals (chickens) and non-target species (ducks, geese) as well as in mammals (mice).Additionally, histopathological slides confirmed that the vaccine is safe for all tested species. Further studies evaluated the potential of rNDV-IBV-T/B to spread horizontally and vertically postimmunization, and its environmental safety. The findings revealed that the vaccine candidate lacks the capability for both horizontal and vertical transmission and does not survive in the environment. In conclusion, the rNDV-IBV-T/B strain is safe and holds potential as a new chimeric live vaccine for ND and IB.